The The Influence Of Selling Price And Product Brand On Consumer Purchase Interest (Case Study At The Sukabumi Tiger Cell Counter) - Muhammad Rico Pratama; Tina Miniawati Barusman (Cita konsultindo, 2024)
This research was conducted to analyze the influence of selling price and product brand on purchasing interest among consumers and visitors to the Tiger Cell Sukabumi counter. The objectives of this research are: to analyze the influence of selling price on buying interest, to analyze the influence of product brand on buying interest, and to analyze the influence of selling price and product brand on buying interest. This research is quantitative research with associative methods, causal relationships. The population in this study were visitors and buyers at the Tiger Cell Sukabumi counter in 2023. The number of respondents taken in this study was 77 people, using the slovin formula. The data analysis used was instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing using the Statistical Program for Social Science (SPSS) version 25.0. The analysis results from the t test prove that the Selling Price variable has a positive and significant effect on Purchase Interest. The Product Brand variable has a positive and significant effect on Purchase Interest. Meanwhile, the results of the analysis from the F test prove that the Selling Price (X1) and Product Brand (X2) variables together have a significant effect on Purchase Interest (Y).